Can AI Language Models Improve Human Sciences Research? A Phenomenological Analysis and Future Directions - Marika D'Oria (University of Bologna, 2023)
The article explores the use of the "ChatGPT" artificial intelligence language model in the Human Sciences field. ChatGPT uses natural language processing techniques to imitate human language and engage in artificial conversations. While the platform has gained attention from the scientific community, opinions on its usage are divided. The article presents some conversations with ChatGPT to examine ethical, relational and linguistic issues related to human-computer interaction (HCI) and assess its potential for Human Sciences research. The interaction with the platform recalls the "uncanny valley" phenomenon still known to Social Robotics. While ChatGPT can be beneficial, it requires proper supervision and verification of its results. Furthermore, new research methods must be developed for qualitative, quantitative, and mixed methods.